Black carbon as a compound agricultural stressor: impacts on plant physiology, crop productivity, and agricultural sustainability - Brindha Prasad; Jothimani Palanisamy; S. K. Rajkishore; P. Renukadevi; M. Kavitha; Muthamizh Selvan Annadurai (Plant Cell Reports, 2026)

Effect of increasing temperatures on duckweed growth, photosynthetic performance and frond ontogenesis - Muhammad Irfan; Muhammad Adil Chaudhry; Manuela Bog; Sándor Szabó; Ilona Mészáros; Marcel A. K. Jansen; Viktor Oláh (Plant Cell Reports, 2026)
Key message Duckweeds offer a suitable platform to study the effects of elevated temperatures on aquatic plants, and chlorophyll fluorescence imaging can reveal frond-level distribution of temperature stress. Abstract Temperature rise associated with climate change poses a major challenge for aquatic plants. It has a strong influence on their physiological performance and, consequently, their competitive ability and fitness. Yet comparative studies of impacts on different species remain scarce. This study investigated the effects of four different temperature regimes between 20 and 35 °C on five duckweed species ( Spirodela polyrhiza , Landoltia punctata , Lemna gibba , Lemna minor and Lemna minuta ) by integrating growth- and photosynthesis-based parameters. We also recorded spatial patterns of photosystem II efficiency within fronds using chlorophyll a fluorescence imaging to understand how temperature stress is distributed throughout the frond development. The results highlighted substantial inter-specific variation in thermal responses and underscore the importance of integrating physiological and growth-based indicators to predict aquatic plants’ responses to climatic warming. Through simultaneous measurement of growth performance, photosynthetic efficiency and within-frond heterogeneity, this study provides mechanistic insights into how rising temperatures may influence duckweeds. Such knowledge is essential for predicting future shifts in freshwater primary productivity, species dominance, biological invasions and ecosystem stability under the current global warming scenario.

Exogenous kinetin mitigates arsenic-induced oxidative stress by regulating ROS homeostasis and antioxidant defense in Ocimum basilicum L. - Asif Hussain Hajam; Mohd Soban Ali; Sumit Kumar Singh; Umra Sheikh; Gausiya Bashri (Plant Cell Reports, 2026)

A current view on the involvement of protein phosphatase PP2A subunits in the responses of plants to abiotic stress at the subcellular level - Csaba Máthé; Márta M-Hamvas; Tamás Garda; Zoltán Kónya (Plant Cell Reports, 2026)
PP2A is the most abundant member of the non-metal-dependent serine-threonine phosphatases in eukaryotes. It is an important player in the reversible phosphorylation of proteins and involved in a wide variety of cellular processes, from signal transduction events to cell cycle regulation and a large number of metabolic processes. At the subcellular level, there is a comprehensive knowledge on PP2A-mediated regulation of chromatin and cytoskeletal organization and there is increasing evidence for its relevant functions in the organization of membrane compartments. Relatively little is known about the related regulatory functions of this enzyme complex in the responses of plants to abiotic stresses. However, recent research has revealed several aspects of these relationships at the subcellular level, mainly for osmotic/salt and heat stress. PP2A is a family of three-subunit holoenzyme complexes, where “A” are scaffolding, “B” are regulatory and “C” are catalytic subunits. Here we discuss the involvement of all these subunits in the regulation of stress-related changes in chromatin, cytoskeleton (microtubule and microfilament), endomembrane (including ER) and plastid/mitochondrial organization and emphasize how they sustain the functioning of plant cells under multiple abiotic stresses. There are crucial subunits in this respect, for example A1, C3 and C4 as well as “B” regulatory subunits such as FASS and members of the B and B’ subfamilies. PP2A is involved in stress hormone (featuring ABA) signaling at multiple levels. In light of recent research, we show that different PP2A holoenzymes link together diverse stress-related signaling mechanisms.

Asparagine Synthetase 1 regulates rice seminal root elongation via jasmonic acid metabolism - Shen Zhang; Yuanming Xie; Yuanda Lv; Zhipeng Gao; Xiaofeng He; Yuan Xu; Ruyi Qin; Wei Xuan; Hongchun Xiong; Luxiang Liu; Le Luo; Guohua Xu (Plant Cell Reports, 2026)

Ethylene networking in fruit ripening: molecular mechanisms, hormone crosstalk, climate interactions, and postharvest management - Mostafa Saeed; Mohamed A. Elsadek; Zheng Ruan; Ahmed Alabd (Plant Cell Reports, 2026)